Theory of machines - Rattan, S S. (McGraw-Hill Education (India) Private, 2014)
This book is meant for two semester course on kinematics and dynamics of machinery for undergraduatestudents. The fourth edition of this hallmark textbook continues to provide complete coverageon essentials of kinematics and dynamics of machines with updated coverage on new mechanisms.